The Spiritual Corridor of Mustang: Exploring Chhuksang and Muktinath through Guru Padmasambhava’s Perspective - Gurung, Nir Bahadur (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
This article explores the profound historical and religious connection between Chhuksang, a sacred village in Mustang, Nepal, and Muktinath, a revered pilgrimage site in the Muktinath Valley, through the lens of Guru Padmasambhava’s enduring legacy. Drawing upon historical records, oral traditions, and religious texts, the study highlights the role of Mustang as a spiritual corridor linking Tibetan Buddhist tantric practices centred in Chhuksang with the Hindu-Buddhist syncretism embodied at Muktinath. Here, this article deals with the trade cum pilgrimage passes that were connected the concerned sites, to emphasize Guru Padmasambhava’s relevance as unifying force in correlating Vajrayāna with Vedic rituals and practices. Along with this, I am also going to highlight the continued spiritual practices, rituals, and cultural exchanges that have preserved and invigorated the shared heritage of Chhuksang and Muktinath by situating these sites in Himalaya’s religious landscapes to understanding the dynamic chemistry between geography, spirituality, and cultural identity in Mustang’s sacred landscape.